Wireless secure enhancement with cooperative jamming - Li-juan ZHANG; Zhi-hong LIU; Hong-bo ZHANG; Yong ZENG; Jian-feng MA (Tongxin xuebao)
Secrecy capacity of intrinsically secure communication graph (iS-Graph) can be increased by reducing the signal quality of eavesdroppers with adding controlled interferences.The transmission of secret messages over wireless channels in which the legitimate nodes were aided by cooperative jamming was studied,and a secure communication graph with jamming,jS-Graph was proposed.First,the security properties of jS-Graph was characterized.Then,jamming strategies to confuse eavesdroppers were proposed.To tackle the nearby eavesdropper problem,a two-stage cooperative jamming strategy to jam the eavesdroppers near the source or the destination was applied.The results demonstrate that,with the aid of cooperative jamming the secure communication graph can lead to secrecy gains.These results help to clarify how the presence of eavesdroppers and the cooperative jamming can influence secure connectivity in wireless networks.